History of the Sabbath and first day of the week - Andrews, John Nevins, 1829-1883 (Salt Lake City, UT : Project Gutenberg, 2022)
"History of the Sabbath and First Day of the Week" by John Nevins Andrews is a historical account written in the late 19th century. The book explores the significance, origins, and adherence to the Sabbath, particularly emphasizing the seventh day as sacred from the creation onward. It also addresses the evolution and historical context surrounding Sunday observance, examining the biblical and secular records of both days. The opening of the text sets the stage for a comprehensive examination of the Sabbath's history, detailing its divine appointment at creation when God rested on the seventh day. Andrews argues that this observance was intended for all humanity from the beginning, establishing its fundamental connection to the commandments given to Adam and reaffirmed through sacred history. The author aims to carefully document the transitions and influences that led to the diminished status of the Sabbath and the rise of Sunday observance, preparing the reader for a detailed exploration of theological, cultural, and historical shifts across centuries. (This is an automatically generated summary.)
Release date is 2022-08-08
Brian Wilson and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Sunday; Seventh-Day Adventists -- Doctrines; Sabbath